Insights into structure, dynamics and hydration of locked nucleic acid (LNA) strand-based duplexes from molecular dynamics simulations - Pande, Vineet (Oxford University Press, 2008)
Locked nucleic acid (LNA) is a chemically modified nucleic acid with its sugar ring locked in an RNA-like (C3′-endo) conformation. LNAs show extraordinary thermal stabilities when hybridized with DNA, RNA or LNA itself. We performed molecular dynamics simulations on five isosequential duplexes (LNA–DNA, LNA–LNA, LNA–RNA, RNA–DNA and RNA–RNA) in order to characterize their structure, dynamics and hydration. Structurally, the LNA–DNA and LNA–RNA duplexes are found to be similar to regular RNA–DNA and RNA–RNA duplexes, whereas the LNA–LNA duplex is found to have its helix partly unwound and does not resemble RNA–RNA duplex in a number of properties. Duplexes with an LNA strand have on average longer interstrand phosphate distances compared to RNA–DNA and RNA–RNA duplexes. Furthermore, intrastrand phosphate distances in LNA strands are found to be shorter than in DNA and slightly shorter than in RNA. In case of induced sugar puckering, LNA is found to tune the sugar puckers in partner DNA strand toward C3′-endo conformations more efficiently than RNA. The LNA–LNA duplex has lesser backbone flexibility compared to the RNA–RNA duplex. Finally, LNA is less hydrated compared to DNA or RNA but is found to have a well-organized water structure.